Petrological characteristics of Algyő-Ferencszállás-Makó area granitoids (Se, Hungary) - Pál Molnár Elemér; Kovács Gábor; Batki Anikó (Department of Mineralogy, Geochemistry and Petrology, University of Szeged Szeged, 2001)
Boreholes located in the axis zone of the uplifted Algyő High (Csongrád Unit, Békésia Terrane, Tisia Composite Terrane, Pannonian Basin) reached granitoid rocks in the Variscan crystalline basement at a depth of 2250-2550 m. On the basis of their textures, these granitoids can be classified in the following two groups: granites of medium-grained, inequigranular, hypidiomorphic-granular texture and meta-granitoid rocks of medium-grained, inequigranular texture with preferred orientation. However, concerning the mineral composition and the texture of the rocks, significant differences cannot be recorded, they are of similar character. The main rock forming minerals of the studied samples are: quartz + microcline ± orthoclase + plagioclase feldspar + biotite + muscovite. Accessory components are apatite, zircone and garnet. Based on their modal composition, the rocks are syenogranites. According to their major element geochemistry, they are granite sensu stricto (syenogranite), subalkaline rocks with a peraluminous character. Concerning their tectonic origin the studied rocks are orogenous, syncollisional, continental collisional granites (CCG). The samples generally display an S-type character with respect to their mineralogy and major element composition.
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok